2008
DOI: 10.1016/j.virol.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of human polyomavirus BK agnoprotein at Ser-11 is mediated by PKC and has an important regulative function

Abstract: The human polyomavirus BK (BKV) genome encodes the capsid proteins VP1 to VP3 and the three regulatory proteins, large and small tumor-antigen and the agnoprotein. Agnoprotein is a phospho-protein, but phosphorylation sites, protein kinases that mediate phosphorylation, and the biological importance of phosphorylation for the life-cycle of BK virus remain unknown. Here, we show that protein kinase C phosphorylates BKV agnoprotein at serine-11. Replacing serine-11 by either non-phosphorylable alanine or phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 61 publications
4
48
0
Order By: Relevance
“…Single or combinatorial mutations at these sites converted JCV in an essentially nonfunctional virus after the first round of replication cycle (Sariyer et al, 2006). Similar work by Johannessen et al, demonstrated the functional importance of the phosphorylated forms of agnoprotein for BKV replication cycle (Johannessen et al, 2008). Analysis of a deletion mutant of BKV agnoprotein by Myhre et al, also showed that BKV has a restricted life cycle in the absence of agnoprotein, but viral function can be rescued when native agnoprotein is provided in trans (Myhre et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Single or combinatorial mutations at these sites converted JCV in an essentially nonfunctional virus after the first round of replication cycle (Sariyer et al, 2006). Similar work by Johannessen et al, demonstrated the functional importance of the phosphorylated forms of agnoprotein for BKV replication cycle (Johannessen et al, 2008). Analysis of a deletion mutant of BKV agnoprotein by Myhre et al, also showed that BKV has a restricted life cycle in the absence of agnoprotein, but viral function can be rescued when native agnoprotein is provided in trans (Myhre et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…This modification plays a significant role in the function of this protein during the viral replication cycle of BK virus and JC virus (Johannessen et al, 2008; Sariyer et al, 2006). SV40 agnoprotein was also previously reported to be phosphorylated but no function was assigned to it (Nomura, Khoury, and Jay, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Agnoprotein is a 71 aa multi-functional protein with numerous reported protein-protein interactions (Darbinyan et al, 2004;Endo et al, 2003;Johannessen et al, 2008;Safak et al, 2002;Suzuki et al, 2005). It also retains a central hydrophobic TMD which, along with an N-terminal region, is required for ER/plasma membrane localization and membrane integration (Suzuki et al, 2010), and forms stable oligomers within infected cells (Coric et al, 2014;Saribas et al, 2011Saribas et al, , 2013Suzuki et al, 2010).…”
Section: Dna Virus Viroporinsmentioning
confidence: 99%
“…Like that of JCV, phosphorylation of BKV agnoprotein at Ser-11 by PKC has also been recently reported to have an important regulatory function (50). Additional recent studies have continued to explore the regulation of BKV at the level of transcriptional control of the NCCR, in particular the notion that cytokines, and the transcription factors that lie downstream of them, may be involved in the regulation of the balance between BKV latency and reactivation.…”
Section: Recent Studies Of Primate Polyomavirusesmentioning
confidence: 99%